Functional lipopolysaccharide receptors of low affinity are constitutively expressed on mouse bone marrow cells. - Girard, R (1997)
Although lipopolysaccharide (LPS)-induced overproduction of cytokines, involved in the pathogenesis of septic shock, occupies the spotlight of endotoxin research, another LPS effect, the differentiation of various cell types including haematopoietic bone marrow cells (BMC), which is probably related to its radioprotective activity, deserves equal attention. We have previously established that nanomolar concentrations of LPS trigger in human BMC the expression of CD14 by an induction mechanism independent of CD14 or any other molecule anchored to the cell membrane by a glycosyl phosphatidylinositol glycolipid. We now show that this LPS-induced stimulation is triggered by the binding of a small number of LPS molecules (13,000 molecules/cell) to constitutive LPS receptors of low affinity (Kd = 480 nM). This interaction, which was inhibited by a synthetic LPS antagonist, appeared specific, reversible, saturable, time- and temperature-dependent, but was independent of divalent cations, and was inhibited by serum. Exposure of BMC to LPS did not induce a down-modulation of these receptors, but enhanced their sensitivity to trypsin degradation. Inhibition of LPS binding following different treatments correlated with inhibition of BMC stimulation, thus suggesting that the sparse constitutive receptors of low affinity are efficient signalling receptors for LPS.